Mubadalah Perspective: A Progressive Reading on Book of Dhau’ Al-Mishbah fi Bayani Ahkam An-Nikah - Mukhammad Nur Hadi (Cyber Media Indonesia, 2020)
This article tries to portray the concept of duties and rights between man and women in the family based on the book of Hasyim Asy’ari (Dhau’ al-Mishbah Fi Bayani Ahkam an-Nikah. By elaborating the theory of reciprocity (mubadalah) created by Faqihuddin Abdul Kodir, this article wants to reinterpret that concept in order to be adjusted to the contemporary condition of how man and women build relation which can be harmonized properly in the household. This article is a normative research using conceptual approach. The writer finds that although there were divisions of rights and duties in detail, but it ideally should be comprehended as a system that one supporting each other. Neglecting the detail job of the spouse will be easily bring the one or the two to harm. Therefore, trying this work to implement the theory is one of the way to build a new narration about what should man and women do in household. Based on Mubadalah perspective, this article show that the concept of duties and rights of both man and woman in household can be implemented. DOI: https://doi.org/10.5281/zenodo.3672389